Editorial Vol15 no3 - Mark Smith (Scottish Journal of Residential Child Care)
Ten years ago it would have been highly unlikely to be publishing a journal issue on a theme of love in the context of children in out of home care. It would have been considered just too left field, dangerous even, in a context of intense anxiety over child abuse. That wider climate has not changed significantly and, if anything, has become more fevered on the back of the Jimmy Savile1 case. What has changed, though, is that sufficient numbers of practitioners, care leavers and academics are developing the confidence to say what is patently obvious to them, both experientially and conceptually - that love is an inevitable feature of child and youth care and is generally a positive one. Jennifer Vincent’s article, which opens this issue, highlights that the importance of love in direct care and educational contexts is recognised and robustly articulated across a range of people professions. Keith White, in the following article, makes the case that someone must use the word love responsibly and healthily in relation to children.